16 Delayed Cord Clamping and Need for Transfusions. (October 2012) - Rabe, H
Abstract : The requirement of donor blood transfusions is a common problem in the treatment of preterm infants, especially below 32 weeks' gestation. Upto 50% of these infants receive at least one transfusion during their hospital stay. Studies on enhancing placento-fetal transfusion have demonstrated a significant increase in circulating blood volume in preterm infants if the cord is either not clamped immediately after birth or is milked several times. The recent updated Cochrane review showed positive benefits of placento-fetal transfusion with regard to better adaptation (e.g. higher blood pressure) after birth as well as reduced intra-ventricular haemorrhage and necrotizing enterocolitis. Infants receiving extra placental blood at birth have a reduced need for donor blood transfusions during the first six weeks of life. The talk will focus on a structured review of the available literature. In addition other preventative measures of anaemia of prematurity such as early protein and iron supplementation will be reviewed.